MANAGEMENT CHALLENGES PRIOR TO SUCCESSFUL TOTAL THYROIDECTOMY IN A PATIENT WITH REFRACTORY GRAVES’ DISEASE - Bin Shudim, Saiful Shahrizal; Bin Ibrahim, Luqman; Vethakkan, Shireene Ratna (Journal of the ASEAN Federation of Endocrine Societies, 2022)
INTRODUCTION Graves’ disease is the most common cause of thyrotoxicosis. Restoration of euthyroidism is vital to prevent further complications including cardiac impairment. Refractory Graves’ disease is uncommon and, thus, poses a challenge in preparing a patient for definitive therapy. We describe a case of refractory Graves’ disease who successfully underwent definitive surgical therapy. CASE A 25-year-old female with a seven-month history of Graves’ disease was referred for recurrent syncope due to multifocal atrial tachycardia. She had multiple previous admissions for severe thyrotoxicosis within the last five months where she was treated with thionamides and multiple five-to-seven-day courses of Lugol’s iodine each time. On admission, thyroid functions tests showed free T4 (fT4) of 92.5 pmol/L (normal range: 11.5 - 22.7) and TSH of <0.01 mIU/L (normal range: 0.55-4.78). The thyroid ultrasound revealed diffuse enlargement of both thyroid lobes with increased vascularity. She was treated with carbimazole up to 80 mg/day, however, fT4 remained at a range of 77.9 – 90.1 pmol/L. Additional therapy with lithium carbonate (1200 mg/day), dexamethasone (8 mg/day) and cholestyramine resin (2 g twice a day) failed to normalize the fT4 level. Switching carbimazole to propylthiouracil (900 mg/day) also did not prove successful. Plasmapheresis was initiated which near-normalized her fT4 after 11 cycles. Tachyarrhythmias were controlled with carvedilol 25 mg twice a day, verapamil 80 mg thrice a day and ivabradine 7.5 mg twice a day. She underwent a successful semi-urgent total thyroidectomy and was eventually discharged after seven days post-operatively with levothyroxine replacement, calcitriol and calcium supplementation. CONCLUSION This case highlights the management challenges in a case of Refractory Graves’ disease. Adjunct to maximal medical therapy, plasmapheresis is a potential modality to achieve a euthyroid state prior to thyroidectomy.